Multiscale analysis of friction behavior at fretting interfaces - Zhinan Zhang; Shuaihang Pan; Nian Yin; Bin Shen; Jie Song (Friction)
Abstract Friction behavior at fretting interfaces is of fundamental interest in tribology and is important in material applications. However, friction has contact intervals, which can accurately determine the friction characteristics of a material; however, this has not been thoroughly investigated. Moreover, the fretting process with regard to different interfacial configurations have also not been systematically evaluated. To bridge these research gaps, molecular dynamics (MD) simulations on Al-Al, diamond-diamond, and diamond-silicon fretting interfaces were performed while considering bidirectional forces. This paper also proposes new energy theories, bonding principles, nanoscale friction laws, and wear rate analyses. With these models, semi-quantitative analyses of coefficient of friction (CoF) were made and simulation outcomes were examined. The results show that the differences in the hardness, stiffness modulus, and the material configuration have a considerable influence on the fretting process. This can potentially lead to the force generated during friction contact intervals along with changes in the CoF. The effect of surface separation can be of great significance in predicting the fretting process, selecting the material, and for optimization.